Challenging frontiers: Canine sporotrichosis due to Sporothrix brasiliensis, first case in Chile - Ailén Dumont; Carlos González; Belén Rivera; Isidora Mercy; Pamela Thomson (Medical Mycology Case Reports, 2024)
We report the first case of Sporothrix brasiliensis in a dog at Santiago, Chile. From an initial biopsy obtained from the patient, a histopathological study was performed that oriented a fungal infection. The molecular diagnosis from the isolated colony confirmed the identity of the S. brasiliensis agent. Although the literature indicates itraconazole as the first treatment option, the patient was treated with terbinafine followed by itraconazole, without achieving a clinical cure. S. brasiliensis that spread rapidly in Latin America, hence highlight the importance of timely diagnosis that contribute to maintaining human and animal health.2012 Elsevier Ltd. All rights reserved.